ANALISIS PERFORMA POSPAY DALAM MENINGKATKAN VOLUME TRANSAKSI DI KANTOR POS CABANG NGAWI - Fauziah , Ahmimurotul; Anifah, Siti (Fakultas Ekonomi Bisnis Islam, 2024)
This study aims to analyze the position of Pospay in increasing transaction volume at the Ngawi Branch Post Office through a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach. Data were collected through interviews and analysis of related documents. The results of the study identified several strengths, such as ease of use and accessibility, which contributed to the increase in transactions. However, weaknesses such as lack of socialization and public understanding were also revealed. Existing opportunities, such as increasing public interest in digital transactions, show potential for growth. On the other hand, threats from competitors and challenges in technological infrastructure are factors that need to be considered. Recommendations from this study include increasing user education and more effective promotions to maximize the potential of Pospay in Ngawi. The results of this study are expected to provide guidance for Post Office managers in optimizing digital services.